PURIFICATION OF GROUND PRODUCED WATER FOR AGRICULTURE IN SUDAN - MUHAMAD YASIN, FARHANA (IRC, 2019)
This research identifies the problem faced in Sudan’s Heglig oilfield onshore drilling activities where production of produced water is rapidly increasing. The problem considered in this research have been approached by focusing on the purification of the ground produced water. Due to low energy consumption and convenience of industrialization, a new technology is proposed which is progressive freeze concentration (PFC) using circulating propeller stirrer motor for produced water treatment. The aim of this project is to remove water from brine using the progressive freeze concentration (PFC) technology. Methods of crystallization follow the same process, beginning with nucleation in the water sample, growth of ice crystals and finally melting of the residual brine to get pure water. To evaluate the performance of the PFC, parameters which are coolant temperature, stirring rate and freezing rate was investigated. The optimum conditions were found to be coolant temperature of - 12oC, stirring rate at 250 RPM and freezing time of 60 minutes.